Biosynthesis of Zinc Oxide Nanoparticles Using Annona Muricata L. Leaf as Antimicrobial - Husna Humaira; Nur Aira Juwita; Muhammad Fauzan Lubis (Jurnal FARMASIMED (JFM), 2026)
Nanotechnology enables the development of materials at the nanometer scale (1–100 nm) with unique physicochemical properties relevant to pharmaceutical applications. Zinc oxide nanoparticles (ZnO NPs) have attracted significant interest due to their semiconductor properties, high catalytic activity, and broad-spectrum antimicrobial potential. However, conventional chemical and physical synthesis methods are often energy-intensive and involve hazardous reagents, necessitating environmentally friendly alternatives. This study aimed to synthesize ZnO NPs via a green biosynthesis approach using Annona muricata L. leaf extract as a natural reducing and stabilizing agent, and to evaluate their physicochemical characteristics and antimicrobial activity. The synthesized ZnO NPs were characterized using UV–Vis spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy–energy dispersive X-ray (SEM–EDX), particle size analysis (PSA), zeta potential analysis, and differential scanning calorimetry (DSC). The results confirmed the successful formation of ZnO NPs with a hexagonal wurtzite crystal structure and an average crystallite size of 26.43 nm. The average hydrodynamic diameter was 489.3 nm, and a zeta potential value of −18.1 mV indicated moderate colloidal stability. DSC analysis revealed endothermic peaks at 162.40 °C and 275.38 °C, corresponding to the removal of residual organic compounds from the plant extract. Antimicrobial evaluation using the disk diffusion method demonstrated concentration-dependent inhibitory activity against Staphylococcus aureus, Staphylococcus epidermidis, and Candida albicans, with the highest inhibition observed at 25 µg/mL. Overall, these findings indicate that ZnO NPs biosynthesized using A. muricata leaf extract possess promising potential as eco-friendly antimicrobial agents for pharmaceutical applications.